Analisis Pertimbangan Majelis Hakim Atas Pelaksanaan Restitusi Terhadap Pemenuhan Hak Anak Korban Tindak Pidanan Pencabulan - Prastya, Tegar; Ismed, Mohamad; Fitrian, Achmad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
In this study, the specific case related to the implementation of restitution in a child sexual abuse case is addressed in Decision Number: 114/Pid.Sus/2023/PN Kot Agung, which has become final and legally binding (Inkracht). The judge did not fully grant the restitution request submitted by the child victim of sexual abuse in the decision. The theories utilized in this research are the Theory of Judicial Consideration and the Theory of Legal Utility.. This research is normative or doctrinal legal research. The approach methods used in this study are analytical, statutory, and case approaches. The types and sources of legal materials utilized involve literature review, collecting secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis in this legal research employs qualitative data analysis.The research findings indicate that the judge's consideration in decisions regarding restitution requests submitted by victims of sexual abuse, through the public prosecutor's indictment in Decision Number 114/Pid.Sus/2023/PN Kot Agung, is based on a thorough evaluation of the evidence presented, the condition of the victim, and the offender's ability to pay restitution. Besides justice in judicial considerations, the principle of legal utility in the judge's assessment of restitution plays a crucial role in ensuring that legal decisions are not only fair but also practically beneficial to the victim. Furthermore, the ideal concept for implementing restitution as a means of fulfilling rights and providing benefits for child victims of sexual abuse should include several essential elements: comprehensive and clear regulations, consistent law enforcement, easy access for victims, transparency and accountability, and prevention and rehabilitation. This ideal concept aims to offer better protection and justice for crime victims and ensure that offenders are held accountable for the impact of their actions